Pengaruh Pemasaran Media Sosial Instagram Dan Electronic Word Of Mouth Terhadap Minat Beli: Studi Pada Teh Pucuk Harum Di Indonesia - Dimas Bayu Anggoro; Murwanto Sigit (Master Manajemen, 2024)
This Research deals with the effect of exposure to Instagram social media advertising, Electronic world of Mouth on buying interest in TehPucuk Harum products. The purpose of this study is to determine the influence between the variables studied such as social media instagram, Electronic world of Mouth, and purchase intention. This research was conducted quantitatively and used a questionnaire as a data collection method. The population was 125 respondents and the research sample used was 125 respondents. The selected population is an Instagram social media user who is a follower of @pucukharumid, as well as a minimum age of 18 years which by law has been declared as the age of legal capacity, and respondents must have seen advertising content for the Teh Pucuk Harum product on Instagram social media. Then sampling using convenience sampling. The techniques in quantitative analysis used in this study are t test, F test, and multiple regression analysis. The results of this study indicate that there is a positive influence between Instagram social media on buying interest, Electronic World of Mouth, has a positive influence with buying interest. The results of this study are expected to help advertisers to find out some of the factors that influence buying interest in Teh Pucuk Harum products on Instagram social media, so that Instagram social media users can have buying interest in Teh Pucuk Harum products.